Hubungan Antara Hafalan Al-Qur’an Dengan Hasil Belajar Bahasa Arab - Budy Saptono; Muhammad Irham; M Zaky Sya’bani (Al Mitsali, 2022)
Arabic is a tool used by humans to communicate. Arabic is a very important survey for every Muslim considering the Qur'an and hadith which are the sources of Islamic religious law in Arabic. Darul Fattah Qur'an Junior High School is one of the schools that makes Arabic a compulsory subject for every student. Based on the results of observations in class VIII of the Takhassus Program at SMP Qur'an Darul Fattah in Bandar Lampung, it shows that the ability to memorize not all students who have memorized the Koran has many high Arabic learning outcomes, and conversely not all students have high learning outcomes. High Arabic has memorized the Qur'an more than students with low Arabic learning outcomes. So there are differences in the ability to memorize students. The formulation of the problem in this study is whether there is a relationship between memorizing Al-Qur'an and the results of learning Arabic for eighth grade students of the Takhassus Program at SMP Qur'an Darul Fattah in Bandar Lampung. This research is a quantitative type, this research design uses a correlation design. This research was conducted at SMP Qur'an Darul Fattah Bandar Lampung. The research sample consisted of 15 students from class VIII of the Takhassus program who were determined using purposive sampling technique. The instruments consist of interviews and documentation. The data analysis technique uses the Product Moment correlation analysis technique. Based on the calculation of the correlation coefficient with a significance level of 5% and 1% with r count> r table or 0.644> 0.514 / 0.641, thus H_ad is accepted. This means that there is a positive relationship between memorizing the Qur'an and learning outcomes in Arabic at 0.644. The level of relationship between memorizing Al-Qur'an and learning outcomes of Arabic for eighth grade students of the takhassus program at SMP Qur'an Darul Fattah Bandar Lampung is in the medium category.